Keindahan Dewi Sri sebagai Dewi Kemakmuran dan Kesuburan di Bali - Putu Maria Ratih Anggraini (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The concept of god for Hindus is described through Nirguna Brahman and Saguna Brahman. The depiction of both is a point of view on the form of god. In agricultural life in Bali, the depiction of the beauty of Dewi Sri as the goddess of rice is depicted as the goddess of prosperity and prosperity and is believed to be the source of all prosperity in the world. Dewi Sri is considered as a spirit who brings joy, happiness and prosperity. The figure of Dewi Sri is always depicted as beautiful, able to fly and always smiling gracefully, depicted not only as the goddess of food, but also a symbol of a beautiful woman, a symbol of the beauty of the earth. In Hindu society in Bali he is also referred to as Sri Sadha, Dewi Danu and Dewa Ayu Manik Galih which are all related to agriculture, food, wealth, prosperity and fertility. Dewi Sri as the goddess of fertility and prosperity is worshiped or simplified by the Hindu community in Bali, especially those who work as farmers and traders.